Borrelia burgdorferi complement regulator-acquiring surface proteins (BbCRASPs): expression patterns during the mammal-tick infection cycle - Bykowski, Tomasz; Woodman, Michael E.; Cooley, Anne E.; Brissette, Catherine A.; Wallich, Reinhard; Brade, Volker; Kraiczy, Peter; Stevenson, Brian (International journal of medical microbiology, 2008)
Host complement is widely distributed throughout mammalian body fluids and can be activated immediately as part of the first line of defense against invading pathogens. The agent of Lyme disease, Borrelia burgdorferi sensu lato (s.l.), is naturally resistant to that innate immune defense system of its hosts. One resistance mechanism appears to involve binding fluid-phase regulators of complement to distinct borrelial outer surface molecules known as CRASPs (complement regulator acquiring surface proteins). Using sensitive molecular biology techniques, expression patterns of all three classes of genes encoding the CRASPs of B. burgdorferi sensu stricto (BbCRASPs) have been analyzed throughout the natural tick-mammal infection cycle. Each class shows a different expression profile in vivo and the results are summarized herein. Studies on the expression of B. burgdorferi genes using animal models of infection have advanced our knowledge on the ability of the causative agent to circumvent innate immune defenses, the contributions of CRASPs to spirochete infectivity, and the pathogenesis of Lyme disease.